Source apportionment of PM2. 5 in Beijing using principal component analysis/absolute principal component scores and UNMIX - Yu Song; Shaodong Xie; Yuanhang Zhang; Limin Zeng; Lynn G. Salmon; Mei Zheng (Science of the Total Environment, 2006)
Source apportionment of fine particulate matter (PM2.5, i.e., particles with an aerodynamic diameter of 2.5 μm or less) in Beijing, China, was determined using two eigenvector models, principal component analysis/absolute principal component scores (PCA/APCS) and UNMIX. The data used in this study were from the chemical analysis of 24-h samples, which were collected at 6-day intervals in January, April, July, and October 2000 in the Beijing metropolitan area. Both models identified five sources of PM2.5: secondary sulfate and secondary nitrate, a mixed source of coal combustion and biomass burning, industrial emission, motor vehicles exhaust, and road dust. On average, the PCA/APCS and UNMIX models resolved 73% and 85% of the PM2.5 mass concentrations, respectively. The results were comparable to previous estimate using the positive matrix factorization (PMF) and chemical mass balance (CMB) receptor models. Secondary products and the emissions from coal combustion and biomass burning dominated PM2.5. Such comparison among various receptor models, which contain different physical constraints, is important for better understanding PM2.5 sources.